Clinical outcome of femoral diaphyseal fractures in adults treated with open verses closed interlocking nail - Mazhar Mahmood; Abdul Hannan; Usama Bin Saeed; Asad Ramzan; Huzaifa Tariq; Hamza Tariq (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: There are different methods for treatment of the long bone fractures, including femoral diaphyseal fractures, ranging from closed intramedullary nail, open intramedullary nail to flexible nail, plating, and external fixator in open type 3 B and 3C fractures. The aim of this study was to compare the functional outcome of open versus closed techniques in treating femoral diaphyseal fractures in skeletally mature adults. METHODOLOGY: A simple observational study was conducted at the Department of Orthopedics, Allied Hospital Faisalabad, from January 2018 to January 2020 with a total of 60 skeletally mature patients with mean age 38.4+1.2 who fulfilled the inclusion criteria were operated, and five patients lost in follow-up. Group A consisted of 27 patients (18 males and 9 females) who were operated with closed interlocking technique. Group B consisted of 28 patients (12 males and 16 females) who were operated with open technique. Both groups were followed prospectively for two years to evaluate the outcome. T-test was used for statistical analysis. RESULTS: The rate of union in group A was better than in group B. Patients in group A had a reunion 1.99±0.86 weeks earlier than group B a significant difference between the two groups with p<0.001. Nonunion occurred in 02(7.40%) patients of group A and 03(10.71%) patients of group B. Only 01 (3.7%) patient from group A and 02 (7.40%) patient of group B suffered from deep infections. CONCLUSION: Closed interlocking for femoral diaphyseal fractures provides earlier reunion of the bone and should be considered the treatment of choice. In case of lack of technical availabilities, open interlocking should be considered as a suitable option.